Tax policy and informal economy within the context of productive government expenditures - Savcı, Çağrı. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
Using a DGE model, the thesis is an attempt to illustrate the dynamics of informal sector in relation to changes in tax policy within the context of productive government expenditures. By the help of calibration exercise, optimal tax system is tried to be explored. Moreover, introducing aggregate uncertainty into the model along technology and tax policy shocks; an attempt has been made to assess the relative ability of the model in exhibiting real business cycle dynamics. The pattern of relationship between tax rates and informality as well as optimum tax burden are observed to be determined to a large extent by government externality level. However, significant welfare gains associated with decreases in income tax rates are still observed for both US and Germany. Secondly, solutions corresponding to Ramsey equilibrium for both economies point to greater efficiency gains associated with the use of taxes on labor compared to the use of taxes on capital income. Thirdly, simulations results suggest that the use of a two-sector model can help to generate higher levels of volatility through capturing the counter-cyclical nature of informal economy. Finally, analysis of elasticities with respect to technology shock shows that higher levels of government externality tend to reinforce income effect in labor supply decision of agents. Moreover, tax policy shocks especially under initially high income tax rates are observed to be better accommodated for higher government externality levels.
Keywords: Expenditures, Public -- Turkey.; Informal sector (Economics) -- Taxation -- Turkey.